(untitled) (Indian Journal of Child Health, 2019)
Objective: The objective of the study was to determine the profile and outcome of children under the age of 12 years admitted with acute poisoning at a tertiary care teaching hospital in Delhi. Materials and Methods: We retrospectively reviewed case files of all patients <12 years of age admitted with poisoning at pediatric emergency from January 2016 to December 2016. All cases with definite history of poisoning were included in the study. Exclusion criteria included chronic poisonings such as lead poisoning, food poisoning, foreign body ingestion, and homeopathic drug ingestion. Baseline characteristics of patients, type of poison, signs and symptoms of poisoning, investigations, treatment, and outcome were recorded from the case files and analyzed. Results: A total of 91 patients were presented with poisoning during the study period. Almost all cases (n=89, 97.8%) were accidental, only 2.2% (n=2) cases were suicidal, and none was homicidal. The mean age of presentation of these patients was 4.08±3.11 years with males outnumbering females (M: F=1.6:1). Corrosives (n=20, 21.9%), kerosene (n=17, 18.7%), prallethrin (n=11, 12.1%), and drugs (n=7, 7.7%) were the most frequently implicated agents. 11 patients (12.1%) were completely asymptomatic, while 30.7% (n=28) patients developed serious symptoms such as breathing difficulty, altered sensorium, seizures, abnormal speech, hematemesis, nasal bleeding, and hypotonia. Gastric lavage was done in 15 cases, three patients received activated charcoal, and three patients required intubation, and one patient required an emergency tracheostomy. One patient expired and rest all survived. Conclusion: The trends of pediatric poisoning noted in our center were different from those observed in other hospital based studies. Corrosives (particularly acids) being the most common agents. Prallethrin, kerosene, and drugs were other common agents.